Respuesta :

We simplify the equation to the form, which is simple to understand
7x-1/2(8x+4)=6
Simplifying:
7x-0.5*(8x+4)=6
Reorder the terms 
7x+(-4x-2)=6
Remove unnecessary parentheses
+7x-4x-2=+6
We move all terms containing x to the left and all other terms to the right.
+7x-4x=+6+2
We simplify left and right side of the equation.
+3x=+8
We divide both sides of the equation by 3 to get x.
x=2.66666666667
1) distribute -1/2
7x - 4x -2 = 6
2) combine like terms
3x - 2 = 6
3) use the addition properties of equality
3x = 8
4) use the division properties of equality
x = 8/3